A 3D printing material for emergency barrier of contaminated sites and preparation method thereof

By using a 3D printing material composed of steel slag powder, calcium carbide slag powder, red mud powder, granular steel slag, basalt fiber balls and water-soluble anionic polyurethane, the barrier formed by printing has low permeability, low diffusion and high flexural strength, solving the problem of insufficient barrier materials in sudden environmental pollution events, and achieving efficient pollutant barriers and powerful mechanical properties.

CN119191760BActive Publication Date: 2025-03-25JIANGSU PROVINCIAL ACAD OF ENVIRONMENTAL SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411390773.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-03-25
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

In sudden environmental pollution incidents, the existing barrier materials have shortcomings in the rapid construction, rapid anti-seepage interception effect, and high mechanical strength and good toughness of barrier barriers, which are difficult to meet the emergency response needs.

Method used

A 3D printing material for emergency barriers on polluted sites is used. The material consists of steel slag powder, calcium carbide slag powder, red mud powder, granular steel slag, basalt fiber balls and water-soluble anionic polyurethane. It is fully mixed by dry method and added with water to prepare a slurry, and then it is fully mixed with water-soluble anionic polyurethane to form a barrier barrier with low permeability coefficient, low diffusion coefficient and high flexural strength.

Benefits of technology

It achieves low permeability, low diffusion and high flexural strength of the barrier barrier, can effectively block pollutants, support repair equipment, has good acid resistance and alkali resistance, strong corrosion resistance, and can reduce the thickness by more than 60%, reducing the amount of raw materials and the amount of solid waste treatment in the later stage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a 3D printing material for emergency barrier of contaminated sites and a preparation method thereof. The 3D printing material includes the following components in terms of mass percentage: first component: 45% to 65%; granular steel slag: 25% to 40%; basalt fiber group: 2% to 10%; water-soluble anionic polyurethane: 2% to 12%; wherein the first component is a mixture of steel slag powder, carbide slag powder and red mud powder. The present invention provides a 3D printing material for emergency barrier of contaminated sites and a preparation method thereof. The barrier formed by printing with the material has low permeability coefficient and diffusion coefficient and high flexural strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of contaminated site remediation, and specifically relates to a 3D printing material for an emergency barrier of a contaminated site and a preparation method thereof. Background Art

[0002] The emergency response to sudden environmental pollution incidents is a difficult problem. Sudden environmental pollution incidents are characterized by uncertainty and concentrated emission of pollutants in a short period of time. If not controlled in time, they will have adverse effects on environmental media such as surface soil, groundwater, and atmosphere, as well as surrounding humans, vegetation, and organisms. Cutting off and controlling pollution sources and preventing the spread of pollution are effective methods for dealing with sudden soil pollution.

[0003] Pollution barriers can effectively control the migration of pollutants or block the exposure pathways of pollutants, and are the most commonly used and effective technology for risk control of polluted sites. Soil-bentonite, cement-bentonite, cement-soil vertical barriers and soil-geomembrane composite horizontal barriers are widely used in risk control projects. However, unlike the risk control of conventional polluted sites, the emergency control and post-disposal of sudden environmental pollution incidents require that the construction of barriers be completed quickly, the anti-seepage and pollution interception effects be quickly exerted, and the mechanical strength and toughness of the barriers be high. Engineering practice shows that soil-bentonite barriers have low strength, cement-bentonite and cement-soil barriers have long maintenance cycles, poor toughness, and are prone to water loss and cracking, resulting in deterioration of service performance. The construction cycle of soil-geomembrane laying is long, and the traffic capacity of large machinery after laying is poor, which makes it difficult to meet the emergency disposal needs of sudden environmental pollution incidents. Therefore, it is urgent to develop high-performance barrier materials that meet the emergency control needs of sudden environmental pollution. Summary of the invention

[0004] The technical problem to be solved by the present invention is: to provide a 3D printing material for an emergency barrier for a contaminated site and a preparation method thereof, wherein the barrier formed by printing with the 3D printing material has low permeability and diffusion coefficient and high flexural strength.

[0005] To solve the above technical problems, the embodiments of the present invention adopt the following technical solutions:

[0006] In a first aspect, an embodiment of the present invention provides a 3D printing material for emergency isolation barrier of a contaminated site, comprising the following components in terms of mass percentage:

[0007] The first component: 45% to 65%;

[0008] Granular steel slag: 25% to 40%;

[0009] Basalt fiber cluster: 2% to 10%;

[0010] Water-soluble anionic polyurethane: 2% to 12%;

[0011] The first component is a mixture of steel slag powder, carbide slag powder and red mud powder.

[0012] As a further improvement of an embodiment of the present invention, in the first component, the mass proportion of steel slag powder is 45% to 70%, the mass proportion of calcium carbide slag powder is 10% to 30%, and the mass proportion of red mud powder is 10% to 30%.

[0013] As a further improvement of the embodiment of the present invention, the particle size of the granular steel slag is 0.8-2.0 mm, and the fineness modulus is 2.30-3.40.

[0014] As a further improvement of the embodiment of the present invention, in the basalt fiber cluster, the length of a single fiber is 4-10 mm and the diameter is 10-20 μm.

[0015] As a further improvement of the embodiment of the present invention, the basalt fiber cluster is composed of two types of fibers uniformly mixed, wherein one type of fiber has a length of 4.0 to 6.0 mm, and the other type of fiber has a length of 6.1 to 10.0 mm.

[0016] As a further improvement of the embodiment of the present invention, in the basalt fiber clusters, the mass of fibers with a length of 4.0 to 6.0 mm accounts for 20% to 45%.

[0017] As a further improvement of the embodiment of the present invention, the pH value of the water-soluble anionic polyurethane is 9.0-10.5.

[0018] In a second aspect, an embodiment of the present invention further provides a method for preparing a 3D printed material for an emergency barrier for a contaminated site, comprising the following steps:

[0019] Step 10, the first component, granular steel slag and basalt fiber mass are fully mixed by dry method, and water is added to prepare slurry;

[0020] Step 20, fully mixing the slurry with water-soluble anionic polyurethane to prepare a 3D printing material for emergency barrier of contaminated sites;

[0021] Wherein, the first component is a mixture of steel slag powder, carbide slag powder and red mud powder;

[0022] The mass proportion of the first component is 45% to 65%, the mass proportion of granular steel slag is 25% to 40%, the mass proportion of basalt fiber clusters is 2% to 10%, and the mass proportion of water-soluble anionic polyurethane is 2% to 12%.

[0023] As a further improvement of the embodiment of the present invention, in step 10, the mass of the added water is 15% to 35% of the total mass of the first component and the granulated steel slag.

[0024] As a further improvement of an embodiment of the present invention, in the first component, the mass proportion of steel slag powder is 45% to 70%, the mass proportion of calcium carbide slag powder is 10% to 30%, and the mass proportion of red mud powder is 10% to 30%.

[0025] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0026] The present invention provides a 3D printing material for an emergency barrier for contaminated sites and a preparation method thereof. The prepared 3D printing material is used for printing to form a barrier, which can effectively solve the shortcomings of long maintenance period, poor toughness, and easy water loss and cracking of soil-bentonite, cement-bentonite, and cement-soil vertical barrier barriers, as well as long construction period and poor large-scale machinery traffic capacity after laying of soil-geomembrane composite horizontal barrier barriers. The material can be used in the construction of emergency barrier barriers for contaminated soil caused by sudden environmental events.

[0027] In addition, compared with the barrier constructed with traditional cement concrete, the barrier formed by printing with the 3D printing material prepared by the present invention has a permeability coefficient reduced by 2 to 3 orders of magnitude and a diffusion coefficient reduced by 1 to 2 orders of magnitude, which can effectively block pollutants; the flexural strength is nearly 35 times higher, which can effectively support the repair equipment; it has good acid and alkali resistance and strong corrosion resistance; the thickness of the barrier can be reduced by more than 60%, which greatly reduces the amount of raw materials used and also reduces the amount of solid waste treatment after the later site restoration. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is described in detail below.

[0029] An embodiment of the present invention provides a 3D printing material for emergency isolation barrier of contaminated sites, which includes the following components in terms of mass percentage:

[0030] The first component: 45% to 65%;

[0031] Granular steel slag: 25% to 40%;

[0032] Basalt fiber cluster: 2% to 10%;

[0033] Water-soluble anionic polyurethane: 2% to 12%;

[0034] The first component is a mixture of steel slag powder, carbide slag powder and red mud powder.

[0035] In the above embodiment, the steel slag powder, carbide slag powder and red mud powder in the first component are cementitious materials, which will undergo hydration reaction and gelation reaction in sequence after mixing with water, gradually transforming from dry powder solid matter into gel material, and gradually hardening during the curing process to form a dense block structure. Compared with traditional cement-based cementitious materials, the cost of steel slag powder, carbide slag powder and red mud powder is lower, about 25-35% of cement-based cementitious materials; and the materials are derived from industrial solid waste, and the carbon emission of raw materials is almost zero, so they are more environmentally friendly than cement-based cementitious materials.

[0036] By adding granulated steel slag, the granulated steel slag is used as a fine aggregate with weak reactivity. The granulated steel slag is mixed with cementitious materials to form mortar, which improves the density and uniformity of concrete. Granular steel slag reduces the volume shrinkage of cementitious materials by dividing the cementitious material slurry, thereby reducing the risk of cracking of the barrier. The water absorption and weak reactivity of granulated steel slag will affect the unit water consumption of 3D printing materials, thereby affecting the water-cement ratio and the strength and durability of the barrier. In addition, the use of granulated steel slag can reduce the amount of cementitious materials used, thereby further reducing costs.

[0037] Considering that the strength and toughness of the structure formed by only using cementitious materials are poor, it is difficult to meet the high-intensity and high-frequency impact of external loads such as equipment and personnel during the emergency disposal of contaminated sites. By adding basalt fibers, the embodiments of the present invention can significantly improve the tensile, compressive, flexural strength and toughness of the cementitious material hardened body. The fibers form a mesh structure in the cementitious material hardened body, which can bridge and limit the development of cracks and improve its durability. The addition of fibers can increase the density of the cementitious material hardened body, reduce permeability, and thus improve its anti-seepage performance.

[0038] By adding water-soluble anionic polyurethane, the toughness of the hardened body of the cementitious material is improved, that is, when subjected to impact or load, it can absorb more energy, thereby improving the impact resistance of the material. In addition, basalt fiber and water-soluble anionic polyurethane can adjust the fluidity, buildability, printable time and other 3D printing performance indicators of the cementitious material, and improve the construction and workability of the printing material.

[0039] Preferably, in the first component, the mass proportion of steel slag powder is 45% to 70%, the mass proportion of carbide slag powder is 10% to 30%, and the mass proportion of red mud powder is 10% to 30%.

[0040] Considering that the hydration activity of steel slag is low, the period of generating gel through hydration is long, and it is difficult to use it for the construction of barrier in emergency scenarios. The embodiment of the present invention uses carbide slag and red mud to jointly stimulate the steel slag to improve its hydration activity. After carbide slag and red mud are dissolved in water, calcium ions, chloride ions and hydroxide ions are released. Under alkaline conditions, the silicates in the steel slag dissolve rapidly, and subsequent hydration reactions and volcanic ash reactions occur to generate hydrated calcium silicate and calcium sulfonate. After the oxidation process, the calcium sulfonate as a crystal nucleus is gradually wrapped by the hydrated calcium silicate to form a stabilized gelled substance, which gradually hardens. By optimizing the ratio of the three, the dosage of hydrated calcium silicate and calcium sulfonate can be effectively adjusted to make the hardened gel more dense.

[0041] Preferably, the particle size of the granular steel slag is 0.8-2.0 mm, and the fineness modulus is 2.30-3.40.

[0042] The particle size and gradation of granular steel slag have a significant impact on the construction and workability (such as fluidity, buildability, and printable time) of 3D printing materials. Appropriate fine aggregate content and particle size distribution help improve the construction performance of concrete. Compared with conventional cement mortar, the fine aggregate in the embodiment of the present invention is granular steel slag, not quartz sand; the cementitious material is composed of steel slag powder, carbide slag powder, and red mud powder, rather than cement-based materials. Since granular steel slag has weak reactivity, the water-cement ratio of the printed material can be appropriately increased by using the above-mentioned particle size and fineness modulus, thereby improving the density of the hardened body of the cementitious material. In addition, after the granular steel slag undergoes a hydration reaction, its volume will decrease, so the volume of fine aggregate in the hardened body is not the same as the volume at the initial mixing; and the water and calcium silicate formed on the surface of the steel slag particles that undergo a hydration reaction diffuse with the water and calcium silicate generated by the hydration reaction of the steel slag powder to form a whole, thereby significantly improving its strength.

[0043] Preferably, in the basalt fiber group, the length of a single fiber is 4 to 10 mm and the diameter is 10 to 20 μm. The 3D printing material of this embodiment is composed of aggregate and gel material. The tensile, compressive, flexural strength and toughness of the hardened body of the gel material are significantly improved by adding basalt fibers. The fibers form a mesh structure in the hardened body of the gel material, which can bridge and limit the development of cracks and improve its durability. By reasonably setting the length of the fiber, the mechanical interlocking effect of the fiber and the aggregate in the barrier can be adjusted to increase the mechanical properties of the composite structure. The stress borne on the fiber is transmitted to the hardened slurry, reducing the number and size of cracks and internal microcracks in the barrier, and improving the continuity of the barrier. In the process of force, the fiber changes the stress field of the hardened slurry, and the bridging effect of the fiber is used to prevent or delay the expansion of cracks, thereby improving the toughness of the barrier under the external load during emergency disposal. If the fiber length or diameter is too large, it will form agglomerates and produce holes in the barrier; if the fiber length or diameter is too small, effective friction cannot be formed and the mechanical locking effect is not obvious.

[0044] Further preferably, the basalt fiber group is composed of two kinds of fibers uniformly mixed, one of which has a length of 4.0 to 6.0 mm and the other has a length of 6.1 to 10.0 mm. Preferably, in the basalt fiber group, the mass of fibers with a length of 4.0 to 6.0 mm accounts for 20% to 45%. The fibers adjust the stress state of the composite structure through the bite action with the aggregate in the 3D printing material and the bonding action with the gel material, so its length is closely related to the strength of the bite action and the bonding action. At the same time, the printing material is a non-homogeneous material. By adding fibers of different lengths respectively, the spatial distribution of the fibers can be effectively adjusted, so that the spatial distribution of the network structure formed by the fibers in the hardened body is more uniform, and the bite action and bonding action of the fibers in the axial direction are more uniform, thereby effectively improving the local stress change of the barrier under the external impact, causing the barrier to crack.

[0045] Preferably, the pH value of the water-soluble anionic polyurethane is 9.0 to 10.5. After the polyurethane is added to the gelling material, the flexible chain segments penetrate into the pores of the gelling material by diffusion, forming a physical anchoring and filling effect, thereby enhancing the density and durability of the gelling material. The pH of the water-soluble anionic polyurethane not only determines the content of active groups in the material, but also determines the ease with which it reacts chemically with the hydroxyl group (-OH) of the hydration reaction product of the gelling material after being mixed with the gelling material. Therefore, adding a polyurethane with a pH value of 9.0 to 10.5 to the gelling material improves the dispersibility of the polyurethane and its compatibility with the gelling material, thereby improving the service performance of the barrier.

[0046] The embodiment of the present invention also provides a method for preparing a 3D printing material for an emergency barrier of a contaminated site, comprising the following steps:

[0047] Step 10: The first component, granular steel slag and basalt fiber agglomerates are fully mixed by dry method, and water is added to prepare slurry.

[0048] Step 20, fully mixing the slurry with water-soluble anionic polyurethane to prepare a 3D printing material for emergency barrier of contaminated sites.

[0049] The first component is a mixture of steel slag powder, carbide slag powder and red mud powder.

[0050] The method of this embodiment adopts dry mixing to mix the first component, granular steel slag and basalt fiber clusters, which can effectively avoid the basalt fiber cluster phenomenon caused by wet mixing, thereby causing local stress concentration in the barrier and generating cracking risks; in addition, the dry mixing method can effectively achieve the uniform distribution of the powder component in the first component on the surface of the granular steel slag. Under the action of electrostatic suction, the powder in the first component is firmly combined with the granular steel slag, which provides convenience for the rapid release of hydroxide on the surface of the steel slag after the material comes into contact with water. If wet mixing is adopted, the surface of the granular steel slag absorbs water quickly, and under the action of water molecules, the surface energy of the granular steel slag is reduced, making it difficult to achieve a homogeneous distribution of the powder in the first component on the surface of the granular steel slag, and it is difficult to achieve the expected activation effect.

[0051] The mass proportion of the first component is 45% to 65%, the mass proportion of granular steel slag is 25% to 40%, the mass proportion of basalt fiber clusters is 2% to 10%, and the mass proportion of water-soluble anionic polyurethane is 2% to 12%. Preferably, in the first component, the mass proportion of steel slag powder is 45% to 70%, the mass proportion of calcium carbide slag powder is 10% to 30%, and the mass proportion of red mud powder is 10% to 30%.

[0052] Preferably, in step 10, the mass of water added is 15% to 35% of the total mass of the first component and the granular steel slag. The moisture content is a key indicator for controlling the fluidity and constructability of the printing material, and also determines the pollution interception and load-bearing performance of the barrier. The fine aggregate of the 3D printing material of this embodiment is granular steel slag, which has weak reactivity and water absorption. After encountering water, the granular steel slag absorbs part of the water, and a hydration reaction will occur, consuming part of the pore water. The above-mentioned water addition rate is adopted in this embodiment, which can fully guarantee the excellent printing performance and service performance of the printing material.

[0053] Four examples and seven comparative examples are provided below.

[0054] Example 1

[0055] Step 1: 2250g of the first component, 2000g of granular steel slag and 3g of basalt fiber mass are fully mixed by dry method, and 637.5g of water is added to prepare a slurry. In the first component, the mass proportion of steel slag powder is 45%, the mass proportion of calcium carbide slag powder is 30%, and the mass proportion of red mud powder is 25%. The basalt fiber mass contains two types of fibers, both with a diameter of 10μm, one fiber length is 4.0mm, accounting for 20% by mass, and the other fiber length is 6.1mm. The particle size of the granular steel slag is 0.8-2.0 mm, and the fineness modulus is 2.30-3.40.

[0056] Step 2: fully mix the slurry with 600 g of water-soluble anionic polyurethane with a pH value of 9.0 to prepare a 3D printing material for emergency barrier of contaminated sites.

[0057] The material was placed in a standard curing environment. After curing for 2 hours, the specimen was demoulded and shaped to meet the test requirements, and the curing was continued for 2 days.

[0058] Example 2

[0059] Step 1: 3250g of the first component, 1150g of granular steel slag and 500g of basalt fiber mass are fully mixed by dry method, and 1540g of water is added to prepare a slurry. In the first component, the mass proportion of steel slag powder is 60%, the mass proportion of calcium carbide slag powder is 10%, and the mass proportion of red mud powder is 30%. The basalt fiber mass contains two types of fibers, both with a diameter of 20μm, one fiber length is 6mm, accounting for 45% by mass, and the other fiber length is 10mm. The particle size of the granular steel slag is 0.8-2.0 mm, and the fineness modulus is 2.30-3.40.

[0060] Step 2: fully mix the slurry with 100 g of water-soluble anionic polyurethane with a pH value of 10.5 to prepare a 3D printing material for emergency barrier of contaminated sites.

[0061] The material was placed in a standard curing environment. After curing for 2 hours, the specimen was demoulded and shaped to meet the test requirements, and the curing was continued for 2 days.

[0062] Example 3

[0063] Step 1: 2500g of the first component, 1500g of granular steel slag and 500g of basalt fiber mass are fully mixed by dry method, and 1200g of water is added to prepare a slurry. In the first component, the mass proportion of steel slag powder is 70%, the mass proportion of calcium carbide slag powder is 20%, and the mass proportion of red mud powder is 10%. The basalt fiber mass contains two types of fibers, one with a length of 4mm, a diameter of 10μm, and a mass proportion of 30%, and the other with a length of 10mm and a diameter of 20μm. The particle size of the granular steel slag is 0.8-2.0mm, and the fineness modulus is 2.30-3.40.

[0064] Step 2: fully mix the slurry with 500 g of water-soluble anionic polyurethane with a pH value of 10 to prepare a 3D printing material for emergency barrier of contaminated sites.

[0065] The material was placed in a standard curing environment. After curing for 2 hours, the specimen was demoulded and shaped to meet the test requirements, and the curing was continued for 2 days.

[0066] Example 4

[0067] Step 1: 3250g of the first component, 1250g of granular steel slag and 100g of basalt fiber mass are fully mixed by dry method, and 1125g of water is added to prepare a slurry. In the first component, the mass proportion of steel slag powder is 60%, the mass proportion of calcium carbide slag powder is 10%, and the mass proportion of red mud powder is 30%. The basalt fiber mass contains two types of fibers, both with a diameter of 15μm, one fiber length is 5mm, accounting for 35% by mass, and the other fiber length is 8mm. The particle size of the granular steel slag is 0.8-2.0 mm, and the fineness modulus is 2.30-3.40.

[0068] Step 2: Fully mix the slurry with 400 g of water-soluble anionic polyurethane with a pH value of 9.5 to prepare a 3D printing material for emergency barrier of contaminated sites.

[0069] The material was placed in a standard curing environment. After curing for 2 hours, the specimen was demoulded and shaped to meet the test requirements, and the curing was continued for 2 days.

[0070] Comparative Example 1

[0071] The first component in Example 1 was replaced with ordinary Portland cement, and the rest was the same as Example 1.

[0072] Comparative Example 2

[0073] The granular steel slag is replaced by quartz sand, the quartz sand particle size is 0.8-2.0 mm, the fineness modulus is 2.30-3.40, and the rest is the same as in Example 1.

[0074] Comparative Example 3

[0075] In this comparative example, no basalt fiber mass is added. In 5 kg of raw materials, the first component accounts for 48%, the mass of granular steel slag accounts for 40%, the mass of water-soluble anionic polyurethane accounts for 12%, and the rest is the same as in Example 1.

[0076] Comparative Example 4

[0077] In this comparative example, no water-soluble anionic polyurethane is added. In 5 kg of raw materials, the first component accounts for 57% by weight, the granular steel slag accounts for 40% by weight, and the basalt fiber group accounts for 3% by weight. The rest are the same as in Example 1.

[0078] Comparative Example 5

[0079] The basalt fiber cluster of this comparative example contains only one type of fiber, with a diameter of 10 μm and a fiber length of 4.0 mm. The rest is the same as that of Example 1.

[0080] Comparative Example 6

[0081] In this comparative example, the first component, granular steel slag, basalt fiber agglomerates, water-soluble anionic polyurethane and water are mixed once by wet method. The rest is the same as in Example 1.

[0082] Comparative Example 7

[0083] The first component of this comparative example does not contain red mud powder, steel slag accounts for 50% by weight, and carbide slag powder accounts for 50% by weight. The rest is the same as Example 1.

[0084] The samples made from the above four examples and seven comparative examples were tested. The permeability coefficient of the samples was tested in accordance with the "Testing Procedure for Hydraulic Plastic Concrete" (DL / T 5303-2013), the oxygen diffusion coefficient of the samples was tested in accordance with the test method adopted by Zhou Luquan (Experimental Technology and Management, 2018, 35 (07): 117-120.), and the flexural strength was tested in accordance with the "Testing Method for Cement Mortar Strength (ISO Method)" (GB / T 17671-1999). The test results of the relevant samples are shown in Table 1.

[0085] Table 1 Test results of service performance parameters of barrier barriers in examples and comparative examples

[0086] Sample Permeability coefficient (cm / s) <![CDATA[Diffusion coefficient (m 2 / s)]]> Flexural strength (MPa) Example 1 <![CDATA[1.27×10 -7 ]]> <![CDATA[6.09×10 -7 ]]> 6.72 Example 2 <![CDATA[2.52×10 -7 ]]> <![CDATA[6.77×10 -7 ]]> 5.91 Example 3 <![CDATA[2.03×10 -7 ]]> <![CDATA[2.55×10 -7 ]]> 6.51 Example 4 <![CDATA[3.15×10 -7 ]]> <![CDATA[8.92×10 -7 ]]> 6.39 Comparative Example 1 <![CDATA[9.64×10 -7 ]]> <![CDATA[2.37×10 -6 ]]> 4.76 Comparative Example 2 <![CDATA[1.81×10 -6 ]]> <![CDATA[7.24×10 -6 ]]> 5.98 Comparative Example 3 <![CDATA[7.99×10 -7 ]]> <![CDATA[5.25×10 -6 ]]> 3.14 Comparative Example 4 <![CDATA[1.09×10 -6 ]]> <![CDATA[1.92×10 -6 ]]> 6.17 Comparative Example 5 <![CDATA[8.25×10 -7 ]]> <![CDATA[5.11×10 -6 ]]> 4.33 Comparative Example 6 <![CDATA[3.18×10 -6 ]]> <![CDATA[5.59×10 -6 ]]> 3.55 Comparative Example 7 <![CDATA[8.79×10 -7 ]]> <![CDATA[3.14×10 -6 ]]> 4.15

[0087] The permeability coefficients of Examples 1 to 4 are between 1.27×10 -7 ~3.15×10 -7 cm / s, with an average value of 2.21×10 -7 cm / s; diffusion coefficient is 2.55×10 -7 ~8.92×10-7 m 2 / s, with an average value of 5.74×10 -7 m 2 / s, flexural strength 5.91-6.72 MPa, with an average value of 6.32 MPa. It can be seen that the barrier prepared by the 3D printing material of the present invention has low permeability coefficient, low diffusion coefficient and high flexural strength.

[0088] Comparing the average test results of the example with the test results of comparative example 1, it can be found that the permeability coefficient of comparative example 1 increased by 4.36 times, the diffusion coefficient increased by 4.12 times, and the flexural strength was 75.31% of its value. It can be seen that compared with ordinary Portland cement, the service performance of the barrier material of the present invention is much better. The reason is that the water-soluble anionic polyurethane will hinder the hydration reaction of silicate minerals in ordinary Portland cement, while the calcium ions dissolved from the carbide slag in the present invention can combine with polyurethane, effectively alleviating the adsorption of polyurethane on the surface of silicate minerals in steel slag, thereby not significantly affecting the hydration reaction of silicate minerals in steel slag.

[0089] Comparing the average test results of the example with the test results of comparative example 2, it can be found that the permeability coefficient of comparative example 2 increases by 4.36 times, the diffusion coefficient increases by 12.61 times, and the flexural strength is 94.62% of its value. It can be found that the weak hydration reaction of the granular slag in the present invention can promote the improvement of the bonding strength between the fine aggregate surface and the cementitious material, thereby increasing the density of the barrier and reducing its permeability coefficient.

[0090] By comparing the average test results of the example with the test results of comparative examples 3, 4 and 7, it can be found that each raw material of the present invention has its own function. If basalt fiber clusters, water-soluble anionic polyurethane and red mud powder are not added, their service performance will be significantly reduced.

[0091] By comparing the average test results of the example with the test results of comparative example 5, it can be found that the use of two lengths of fibers in the present invention can effectively adjust the spatial distribution of the fibers, so that the spatial distribution of the network structure formed by the fibers in the hardened body is more uniform, and the axial bite and bonding effects of the fibers are more uniform, thereby effectively improving the local stress changes of the barrier under external impact and causing the barrier to crack.

[0092] By comparing the average test results of the example with the test results of comparative example 6, it can be found that the permeability coefficient of the barrier obtained by the staged mixing of the present invention increases by 14.39 times, and the diffusion coefficient increases by 9.74 times. The reason may be that the step-by-step mixing is adopted, and the powder component in the first component is evenly distributed on the surface of the granular steel slag during the dry mixing of the first component and the granular steel slag. Under the action of electrostatic attraction, the powder in the first component is firmly combined with the granular steel slag, which facilitates the rapid release of hydroxide on the surface of the steel slag after the material contacts with water.

[0093] The basic principles, main features and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above specific embodiments, and the descriptions in the above specific embodiments and the specification are only for further illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed for protection.

Claims

1. A 3D printing material for emergency barrier of contaminated sites, characterized in that: According to mass percentage, it includes the following components: The first component: 45% to 65%; Granular slag: 25% to 40%; Basalt fiber cluster: 2% to 10%; Water-soluble anionic polyurethane: 2% to 12%; The first component is a mixture of steel slag powder, carbide slag powder and red mud powder; The particle size of the granular steel slag is 0.8-2.0 mm, and the fineness modulus is 2.30-3.40; In the basalt fiber cluster, a single fiber has a length of 4 to 10 mm and a diameter of 10 to 20 μm; the basalt fiber cluster is composed of two types of fibers uniformly mixed, one of which has a length of 4.0 to 6.0 mm and the other has a length of 6.1 to 10.0 mm.

2. The 3D printing material for emergency barrier of contaminated sites according to claim 1 is characterized in that: In the first component, steel slag powder accounts for 45% to 70% by mass, carbide slag powder accounts for 10% to 30% by mass, and red mud powder accounts for 10% to 30% by mass.

3. The 3D printing material for emergency barrier of contaminated sites according to claim 1 is characterized in that: In the basalt fiber clusters, the mass of fibers with a length of 4.0 to 6.0 mm accounts for 20% to 45%.

4. The 3D printing material for emergency barrier of contaminated sites according to claim 1, characterized in that: The pH value of the water-soluble anionic polyurethane is 9.0-10.

5.

5. A method for preparing 3D printing materials for emergency barrier of contaminated sites, characterized in that: The following steps are involved: Step 10, the first component, granular steel slag and basalt fiber mass are fully mixed by dry method, and water is added to prepare slurry; Step 20, fully mixing the slurry with water-soluble anionic polyurethane to prepare a 3D printing material for emergency barrier of contaminated sites; Wherein, the first component is a mixture of steel slag powder, carbide slag powder and red mud powder; The mass proportion of the first component is 45% to 65%, the mass proportion of granular steel slag is 25% to 40%, the mass proportion of basalt fiber clusters is 2% to 10%, and the mass proportion of water-soluble anionic polyurethane is 2% to 12%; The particle size of the granular steel slag is 0.8-2.0 mm, and the fineness modulus is 2.30-3.40; In the basalt fiber cluster, a single fiber has a length of 4 to 10 mm and a diameter of 10 to 20 μm; the basalt fiber cluster is composed of two types of fibers uniformly mixed, one of which has a length of 4.0 to 6.0 mm and the other has a length of 6.1 to 10.0 mm.

6. The preparation method according to claim 5, characterized in that: In the step 10, the mass of the added water is 15% to 35% of the total mass of the first component and the granulated steel slag.

7. The preparation method according to claim 5, characterized in that: In the first component, steel slag powder accounts for 45% to 70% by mass, carbide slag powder accounts for 10% to 30% by mass, and red mud powder accounts for 10% to 30% by mass.

Citation Information

Patent Citations

  • Environment functional type composite vertical barrier wall

    CN117926860A

  • Preparation method and application of solid waste-based 3D printing concrete

    CN118515456A